Genomic epidemiology of Vibrio cholerae reveals the regional and global spread of two epidemic non-toxigenic lineages. - Haoqiu Wang; Chao Yang; Zhou Sun; Wei Zheng; Wei Zhang; Hua Yu; Yarong Wu; Xavier Didelot; Ruifu Yang; Jingcao Pan; Yujun Cui (Public Library of Science (PLoS), 2020)
Non-toxigenic Vibrio cholerae isolates have been found associated with diarrheal disease globally, however, the global picture of non-toxigenic infections is largely unknown. Among non-toxigenic V. cholerae, ctxAB negative, tcpA positive (CNTP) isolates have the highest risk of disease. From 2001 to 2012, 71 infectious diarrhea cases were reported in Hangzhou, China, caused by CNTP serogroup O1 isolates. We sequenced 119 V. cholerae genomes isolated from patients, carriers and the environment in Hangzhou between 2001 and 2012, and compared them with 850 publicly available global isolates. We found that CNTP isolates from Hangzhou belonged to two distinctive lineages, named L3b and L9. Both lineages caused disease over a long time period with usually mild or moderate clinical symptoms. Within Hangzhou, the spread route of the L3b lineage was apparently from rural to urban areas, with aquatic food products being the most likely medium. Both lineages had been previously reported as causing local endemic disease in Latin America, but here we show that global spread of them has occurred, with the most likely origin of L3b lineage being in Central Asia. The L3b lineage has spread to China on at least three occasions. Other spread events, including from China to Thailand and to Latin America were also observed. We fill the missing links in the global spread of the two non-toxigenic serogroup O1 V. cholerae lineages that can cause human infection. The results are important for the design of future disease control strategies: surveillance of V. cholerae should not be limited to ctxAB positive strains.